2016
DOI: 10.1111/1365-2745.12577
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and functional mechanisms of direct and indirect interactions among alien and native plants

Abstract: Summary1. Disentangling direct and indirect interactions among alien and native plants is essential to understanding the success of alien plants in multispecies communities, but studies have only focused on direct pairwise interactions. Moreover, it is also essential to explore phylogenetic and functional mechanisms driving these interactions. 2. In a greenhouse experiment, we selected nine groups of alien and native plant species from the herbaceous flora of Germany to disentangle their direct and indirect in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 63 publications
2
8
2
Order By: Relevance
“…Possibly, our findings indicate that the large seedlings of large‐seeded species are more likely to survive, but that this is at a cost of reproduction (Díaz et al, ), at least during the period that our experiment lasted. In line with several other studies (e.g., Conti et al, ; Feng & van Kleunen, ), our results showed that the effects of univariate hierarchical functional distance based on plant height or leaf size on the performance of the alien species were positive, whereas those based on SLA were negative. This shows that alien plants are more successful if they are taller and have larger leaves with a lower SLA than the native residents.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Possibly, our findings indicate that the large seedlings of large‐seeded species are more likely to survive, but that this is at a cost of reproduction (Díaz et al, ), at least during the period that our experiment lasted. In line with several other studies (e.g., Conti et al, ; Feng & van Kleunen, ), our results showed that the effects of univariate hierarchical functional distance based on plant height or leaf size on the performance of the alien species were positive, whereas those based on SLA were negative. This shows that alien plants are more successful if they are taller and have larger leaves with a lower SLA than the native residents.…”
Section: Discussionsupporting
confidence: 93%
“…In support of the predictions of Darwin's naturalisation hypothesis, increasing values of the different measures of alien-native distance resulted in enhanced performance (from germination to reproduction) of our five target invasive species. This is in line with some previous studies which also found evidence in support of the hypothesis (Feng & van Kleunen, 2016;Jiang et al, 2010;Strauss et al, 2006), but others showed that the effects of alien-native distances were dependent on whether phylogenetic distance indicates niche preadaptation or competitive interactions, and on the stages of invasion (Diez et al, 2008;Duncan & Williams, 2002;Li, Guo, et al, 2015). Moreover, in our study, the effects of multivariate functional distance were much stronger than those of phylogenetic distance, which suggests that multiple traits-based functional distance is better than phylogenetic distance in capturing niche differences that favour coexistence between the aliens and the native residents.…”
Section: Darwin's Naturalisation Hypothesissupporting
confidence: 94%
See 2 more Smart Citations
“…Most studies, however, focused on pairwise interactions 6 (i.e. interaction between two species; but see refs 7,8 for two exceptions), although in nature most species interact with multiple species. With regard to invasive alien organisms, only few hypotheses guide us in testing interactions among more than two species.…”
Section: Introductionmentioning
confidence: 99%